2020
DOI: 10.1177/0310057x20925827
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional (3D) printed paediatric trachea for airway management training

Abstract: There is a deficit of commercially available paediatric airway models for anaesthesia airway management training, particularly for infant front-of-neck access and customised airway planning. Acknowledging this, we created a three-dimensional printed prototype for an affordable, high-fidelity training device, incorporating realistic tactile feedback, reproducibility and potential for modification for specific patient pathologies. Our model, created on a Stratasys Polyjet J750™ (Rehovot, Israel) printer, is a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Simulation training is not novel in otolaryngology and has been particularly prominent in the otology and rhinology subspecialities, where several studies have demonstrated the positive impacts of simulation models on mastoidectomy and skull base procedures in surgical training [22,23]. This is also reflected in the utilization of 3D printed models for pediatric airway management and laryngeal surgery [24][25][26][27]. The use of simulation models in head and neck oncology has, however, not been as readily adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Simulation training is not novel in otolaryngology and has been particularly prominent in the otology and rhinology subspecialities, where several studies have demonstrated the positive impacts of simulation models on mastoidectomy and skull base procedures in surgical training [22,23]. This is also reflected in the utilization of 3D printed models for pediatric airway management and laryngeal surgery [24][25][26][27]. The use of simulation models in head and neck oncology has, however, not been as readily adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it can directly replicate anatomical structures from medical images into functional anatomical simulators. Moreover, it can combine realistic tactile feedback, repeatability, and the potential for patient-specific pathology modifications [ 184 ]. Finally, it provides training opportunities for anesthesiologists to improve their proficiency in anesthesia operations.…”
Section: Research and Application Of 3d Printing In The Anesthesia Fieldmentioning
confidence: 99%
“…Accordingly, the risks related to airway control operations differ among patients. Three-dimensional printing is customized for airway planning in different populations, including infants [ 186 ], pediatric patients [ 184 , 187 , 188 ], and adult patients, even in specific cases involving congenital or acquired craniofacial anomalies [ 15 ], difficult airway intubation [ 189 ], cricothyroid puncture [ 190 ], thoracic puncture [ 180 ], thoracic epidural analgesia [ 191 ], or control of combined lumbar and epidural anesthesia planes.…”
Section: Research and Application Of 3d Printing In The Anesthesia Fieldmentioning
confidence: 99%
“…We have previously published the use of a 3D printed paediatric trachea for use in airway management training. 7 By further refining our existing technology, we have produced a 3D printed adult trachea incorporating the ability to emulate dynamic pathologies. Adaptation of this has the potential to simulate normal cardiorespiratory movement within the airways.…”
Section: Introductionmentioning
confidence: 99%